Assessing the Impact of Chlorhexidine Mouthwash on Radiation-Induced Oral Mucositis in Head and Neck Cancer Patients: A Pre-Experimental Study - Nikita Kumari Nikita Kumari; Kavita Choudhary (International Journal of Oncological Nursing and Practices, 2025)
Introduction: Cancer poses a major global health threat and is the second leading cause of death worldwide, following cardiovascular diseases, particularly in developed countries. Among cancers, head and neck cancer ranks as the 6th most common, representing about 6% of all cancer diagnoses. One of the frequent side effects of radiotherapy (RT) is mucositis, an inflammation of the mucous membranes. Chlorhexidine, a commonly used antiseptic and disinfectant found in mouthwashes, is known for its ability to reduce oral bacteria and dental plaque. The purpose of this study was to assess the effectiveness of chlorhexidine mouthwash in both preventing and treating oral mucositis in patients receiving radiotherapy for head and neck cancer. Objectives of the study: The objectives of the study were to assess the pre-test and post-test scores of radiation therapy-induced oral mucositis in head and neck cancer patients, to evaluate the effectiveness of chlorhexidine mouthwash in managing radiation therapy-induced oral mucositis in these patients, and to determine the association between pre-test scores and selected socio-demographic and clinical profiles of patients with radiation therapy-induced oral mucositis at the Regional Cancer Centre in PGIMS, Rohtak. Material and Method: A study was conducted using quantitative research approach pre-experimental, one group pre-post-test design. The sample size consisted of 60 participants, selected using a non-randomized convenience sampling technique under non-probability sampling. OMAS (Oral Mucositis Assessment Scale) was used for pre and post-test which is in public domain and free to use. Statistical analysis of data was done by using descriptive and inferential statistic. Result: The mean value of overall pretest score was 24.48, SD value of score was 2.501 whereas mean value of post-test score was 21.25 and SD value of score was 2.289 and. The average difference between the pre-test and post-test scores was 3.233. The results suggest that chlorhexidine had a notable effect in reducing the severity of oral mucositis. The paired 't' test revealed statistically significant results, with a P-value less than 0.05. Conclusion: The results indicated that patients with oral mucositis who used chlorhexidine mouthwash experienced effective healing of the condition.
Keywords: Cancer; Head and neck cancer; chlorhexidine; radiation therapy-induced oral mucositis; radiotherapy (RT)